2003
DOI: 10.1590/s0103-84782003000100011
|View full text |Cite
|
Sign up to set email alerts
|

Variáveis morfogênicas de Andropogon lateralis Nees submetido a níveis de nitrogênio nas quatro estações do ano

Abstract: RESUMO

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
4
3

Year Published

2005
2005
2014
2014

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 6 publications
1
3
4
3
Order By: Relevance
“…lateralis is one of the live components with highest expression in the Pampa biome (Damé et al, 1997), and it did not change leaf elongation rate under N application (Table 2) and this response assumes great importance in pasture management in this biome. For this species, however, when 400 kg ha -1 of N were applied, there was a crescent response in leaf elongation rate until the level of 200 kg ha -1 N (Bandinelli et al, 2003). For the 100 kg ha -1 of N applied in the summer, those authors observed leaf elongation rate 69% higher than the observed in this study (Table 2).…”
Section: Resultscontrasting
confidence: 60%
See 1 more Smart Citation
“…lateralis is one of the live components with highest expression in the Pampa biome (Damé et al, 1997), and it did not change leaf elongation rate under N application (Table 2) and this response assumes great importance in pasture management in this biome. For this species, however, when 400 kg ha -1 of N were applied, there was a crescent response in leaf elongation rate until the level of 200 kg ha -1 N (Bandinelli et al, 2003). For the 100 kg ha -1 of N applied in the summer, those authors observed leaf elongation rate 69% higher than the observed in this study (Table 2).…”
Section: Resultscontrasting
confidence: 60%
“…Morphogenesis studies on native grasses of the Pampa biome have already been conducted (Cruz & Boldrini, 1998;Trindade & Rocha, 2001Eggers et al, 2004) and in some of them, the effect of N fertilization on the morphogenetic traits of some species was evaluated (Denardin, 2001;Bandinelli et al, 2003;Nabinger et al, 2003;Santos, 2004;Quadros & Bandinelli, 2005;Townsend, 2008). In these reports, it was verified that leaf elongation rate is positively related with N.…”
Section: Introductionmentioning
confidence: 99%
“…A importância de compreender que existe uma evolução estacional no tamanho foliar ao longo dos estádios de desenvolvimento se deve ao impacto sobre o balanço entre os fl uxos de crescimento e senescência e, como consequência, na quantidade de forragem disponível em uma pastagem. BANDINELLI et al (2003), avaliando a resposta morfogênica de A. lateralis sob níveis de adubação de N nas quatro estações do ano, observou resposta crescente da TEF até o nível de 200kg N ha -1 , sendo reduzido com 400kg. N ha -1 em todas as estações.…”
Section: Resultsunclassified
“…Para promover práticas de manejo sustentáveis, é necessário o entendimento dos processos de crescimento vegetal por meio de variáveis morfogênicas. O estudo dessas variáveis é ainda restrito a poucas espécies que compõem o Bioma Campos Sulinos, podendo ser citados trabalhos com Andropogon lateralis (BANDINELLI et al, 2003;MACHADO, 2010); Piptochaetium montevidense (MACHADO, 2010); Briza subaristata (DENARDIN, 2001), Paspalum notatum (MACHADO, 2010); Coelorhachis selloana (EGGERS et al, 2004); Paspalum urvillei (QUADROS & BANDINELLI, 2005), Sorghastrum pellitum, Paspalum plicatulum, Aristida laevis, Axonopus affi nis e Saccharum angustifolius (MACHADO, 2010). Todas as avaliações, exceto as de BANDINELLI et al (2003) Os dados meteorológicos se aproximaram às médias históricas com uma variação de 7,4, 5,0 e 11,3% para menos, para temperatura, umidade e precipitação pluviométrica, respectivamente.…”
Section: Introductionunclassified
“…BANDINELLI et al (2003) observaram valores médios dos tratamentos de 0,062 e 0,076 folhas dia -1 para Andropogon lateralis Nees na primavera e verão, respectivamente. E mesmo para espécies de ciclo hibernal, GONÇALVES & QUADROS (2003) observaram valores médios de 0,070 a 0,077 folhas dia -1 para L. multiflorum.…”
Section: Resultsunclassified